Back Complaints in Older Adults: Prevalence of Neuropathic Pain and Its Characteristics. Issue 11 (4th October 2013) - Enthoven, Wendy T. M.; Scheele, Jantine; Bierma‐Zeinstra, Sita M. A.; Bueving, Herman J.; Bohnen, Arthur M.; Peul, Wilco C.; van, Maurits W.; Berger, Marjolein Y.; Koes, Bart W.; Luijsterburg, Pim A. J.
Abstract Objective Neuropathic symptoms are reported in 16–55.6% of patients with back pain. Studies were performed in various populations; however, none focused on older adults. The aim of the study was to assess prevalence of neuropathic pain in older adults with back pain. Methods Prevalence of neuropathic pain, measured with the Dolour Neuropathique en 4 questions (DN4), was assessed in the Back Complaints in the Elders study (Netherlands). Patients (>55 years) consulting their general practitioner with a new episode of back complaints were included. Two DN4‐versions were used: one based on interview plus physical examination, the other based on interview alone. In the interview plus physical examination version, patients' and complaint characteristics were compared between groups with different scores (0, 1, 2, 3, and ≥4). The DN4 interview‐version compared patients with negative and positive scores. Results Of the 261 included patients available for analysis were 250 patients (95.8%) with the DN4 interview plus physical examination, and 259 patients (99.2%) with the DN4 interview. In DN4 interview plus physical examination (N = 250), five patients (2%) scored positive (score ≥4). Higher score was associated with pain radiating below the knee (P < 0.001) and use of paracetamol (P = 0.02). In DN4 interview (N = 259), 29 (11.2%) patients scored positive (score ≥3). Positive score was associated with higher body mass index (P = 0.01), pain radiating below the knee (P = 0.001), and use of paracetamol (P = 0.002). Conclusions In older adults with back pain presenting with a new episode in primary care, prevalence of neuropathic pain is low and seems to be associated with pain radiating below the knee, use of paracetamol, and higher body mass index.